2017
DOI: 10.18632/oncotarget.21234
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between TGF-β1, canonical WNT/β-catenin pathway and PPAR γ in radiation-induced fibrosis

Abstract: Radiation therapy induces DNA damage and inflammation leading to fibrosis. Fibrosis can occur 4 to 12 months after radiation therapy. This process worsens with time and years. Radiation-induced fibrosis is characterized by fibroblasts proliferation, myofibroblast differentiation, and synthesis of collagen, proteoglycans and extracellular matrix. Myofibroblasts are non-muscle cells that can contract and relax. Myofibroblasts evolve towards irreversible retraction during fibrosis process. In this review, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 335 publications
(355 reference statements)
3
135
0
3
Order By: Relevance
“…TGFβ1 in normal conditions inhibits cell growth, promotes differentiation, and induces apoptosis . Further, TGFβ1 and canonical WNT signaling have been reported to stimulate each other through Smad and non‐Smad pathways . As such, the loss of the antiproliferative WNT10B effects in localized PCa may be, in part, mediated through downregulation of TGFβ1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFβ1 in normal conditions inhibits cell growth, promotes differentiation, and induces apoptosis . Further, TGFβ1 and canonical WNT signaling have been reported to stimulate each other through Smad and non‐Smad pathways . As such, the loss of the antiproliferative WNT10B effects in localized PCa may be, in part, mediated through downregulation of TGFβ1.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Further, TGFβ1 and canonical WNT signaling have been reported to stimulate each other through Smad and non-Smad pathways. 47 As such, the loss of the antiproliferative WNT10B effects in localized PCa may be, in part, mediated through downregulation of TGFβ1. However, TGFβ1 is also known to be a primary inducer of EMT 48 which underscores its role as a driver of aggressive disease.…”
Section: But Contrasts With Stromalmentioning
confidence: 99%
“…[16] This gene encodes the alpha 1 chain of collagen VI, which is expressed in the bulge area of the HF and is involved in the development of the HF during embryogenesis, where it is postulated to inhibit Wnt/β-catenin signalling. [74][75][76][77][78] Wnt/β-catenin signalling is essential for normal human HF function [79][80][81] and for stem cell maintenance [82] ; however, it is Selective PPAR-γ receptor modulators may exert antagonistic or agonistic effects, according to the cell type they function in, and act by modulating the cofactor affinity resulting in changes in the transcriptional activation. This is in contrast to full PPAR-γ agonists that lead to the release of the co-repressor complex and co-activator binding, and PPAR-γ antagonists that result in inadequate conformational modulation of the receptor and preventing the connection with the co-activator.…”
Section: The Imp Ortan Ce Of Pparγ For the Bulg E S Tem Cell S Andmentioning
confidence: 99%
“…Interestingly, when Smad2, 3, and 4 were cotransfected, the luciferase activity of wt-miR-139 was more suppressed although more reversed after the mutation of the predicted Smad4-binding site (Figure 5d It has been reported that miR-139 plays a role in the fibrosis process. MiR-139 can target a series of crucial factors in Wnt signaling, which is an essential signaling pathway in TGFβ1-induced fibrosis (Vallée, Lecarpentier, Guillevin, & Vallée, 2017). In human fibroblast IMR-90 and murine lung fibroblasts, miR-139 interference remarkably increased the expression of β-catenin, collagen I, and α-SMA, indicating that miR-139 inhibition promotes the activation of fibroblasts (Y.…”
Section: Smad2/3/4 Complex Inhibits the Transcription Of Mir-139 Bymentioning
confidence: 99%